Utilization of Tidal Land of The Wonogiri Reservoir - Ritohardoyo, Su (Universitas Muhammadiyah Surakarta, 1999)
ManagementÂ of water dam often failures due to the limited attention to the socio-economic activities of the local population. This research is conerned with agricultural land utilization practiced by the local inhabitants in the vicinity of the dam. Special attention is devoted to characteristics and motivation of the farming households, the way in which lands are utilized, as well as the contribution of the activities to the welfare of the households. The research combines secondary data analysis and a household survey. Primary data are collected via a household survey covering a sample of 150 households cultivating the draw down land of the dam. These households are taken by a simple random sampling, representing some 5,890 hhouseholds living in the vicinity of the dam. Data analysis are executed using various statistical techniques in order to test differences and correlation.The study reveals that the tidal areas of the Wonogiri Dam fluctuate from 1,300 to 6,400 hectares, within 1 to 7 moths period per annum. The cultivator of the tidal area consist of the farmer inhabitants of the dam prior to the construction (81,3 percent) and inhabitants of the surrounding areas of the dam and new omers from other areas (18,7 percent). These farming households are pushed to cultivate these lands due to limited control over land resources in their areas of origin ( averaged 1,057 m2). Variations in the areas of origin and motivation in utilizing of the lands do not lead to significant differences in the size of land cultivated in the tidal areas. Most of these lands are devoted to ultivate rice as stapleÂ food (1,470 m2), rather than to cultivate cash crops (palawija) (1,118 m2). Farming techniques employed in these areas are much more simple than those prior to the construction of the dam or those elsewhere at present in the district. The most important factor affecting incomes in this activity is the amount of capital cost spent. These incomes comprises some 60 percent of the farming households.